Dressed not to kill: CD16+ monocytes impair immune defence against tuberculosis. Issue 2 (14th February 2013) - Lugo‐Villarino, Geanncarlo; Neyrolles, Olivier
<x xml:space="preserve">Abstract</x> Monocytes are blood leukocytes that can differentiate into several phagocytic cell types, including DCs, which are instrumental to the inflammatory response and host defence against microbes. A study published in this issue of the European Journal of Immunology by Balboa et al. [Eur. J. Immunol. 2013. 43: 335‐347] suggests that a shift of the CD16− monocyte population toward a CD16+ subpopulation may represent an immune evasion strategy that ultimately favors persistence of Mycobacterium tuberculosis. Together with other recent reports, the article by Balboa et al. sheds new light on the function of CD16+ monocytes in health and disease; in this commentary, we discuss the implications stemming from these findings.